Mechanical and physical properties of lignocellulosic plastic composite from hybrid sugarcane baggase and mixed tropical hardwood / Nurfatiha Zainal Abidin - Zainal Abidin, Nurfatiha (2020)
Production of Lignocellulosic Plastic Composite (LPC) using wood wastes and agricultural waste is the best way to use waste for beneficial use. Hence, the use of waste and fibers from agricultural waste as an alternative to natural wood for the manufacture of Lignocellulosic Plastic Composite. The aim of the study was to determine the effect of filler loading and types of filler on the mechanical & physical properties of lignocellulosic plastic composite. Four types of filler used are Neat Polypropylene (PP), Sugarcane Bagasse, Mixed Tropical Hardwood and Hybrid Composite (combination of Sugarcane Bagasse and Mixed Tropical Hardwood). In this study, three filler loading were used 10% filler loading, 15% filler loading and 20% filler loading with different types of filler loading. Types of filler and filler loading were main factors that affect the mechanical & physical properties of lignocellulosic plastic composite in this study. There are two types of testing that have been conducted such as mechanical testing and physical testing. The mechanical testing which included tensile testing and bending testing while physical testing including water absorption testing (WA) and thickness swelling testing (TS). The result had shown that filler loading had significant effect on tensile MOE and thickness swelling. For the types of filler, only bending MOE have significant effect. The interaction between filler loading and types of filler shows only tensile MOE have significant effect. At higher filler loading, mechanical properties such as tensile MOE and tensile MOR had showed highest value as compared to lower of filler loading. However, bending MOR was showed opposite effect. Physical properties such as water absorption and thickness swelling was increased at higher filler loading.